Student Perceptions of Problem-Based Learning: A Case Study of Undergraduate Applied Agrometeorology. (21st May 2013) - De Wet, Linda; Walker, Sue
Abstract : Many students do not seem to transfer their learning during formal education into applications in the real world. The objective of this ongoing study was to investigate the opinion of third-year students concerning their program through problem-based learning and to improve the module where necessary. Students attending theory classes had to apply their newly gained knowledge coupled with real-life weather data to solve a problem during practicums. Students attending practicums were given the same questionnaire thrice; thus, the answers were based on different sets of exercises. Responses by attendees for the three questionnaires were 73%, 100%, and 61%, respectively. Students preferred problem-based practicums (78%, 54%, and 72%, resp.) to other non-problem-based practicums. Most students thought that their knowledge had improved and it had prepared them better for the workplace (85%, 77%, and 92%, resp.). Generally students preferred working in groups (74%, 62%, and 56%, resp.), in contrast to those preferring to work individually. Students benefited from problem-based learning in that they thought they had improved their knowledge, skills, and critical thinking abilities and felt that they had learnt things that they could carry into their future lives out in the world at large and the workplace.